Publicar / assinar em redes móveis Ad Hoc - Cristiano Gato de Rezende (2007)
The development of portable computational devices raised new network models which demand different solutions to the ones applied to the traditional model where every terminal of the network is fixed. The most chaotic model is the mobile ad hoc network, MANET, where there is not any infra-structure previously available. For this reason, every communication has to be done between devices which radios reach each other. This model present many challenges like energy, processing and bandwidth restriction, intermittent connection and difficulties on routing messages.The Publish/Subscribe paradigm offers decoupling dimensions (time, space and synchronization) which helps the communication process on MANETs. However, implanting an architecture in such model requires solutions different from those usually developed. Solutions adequate to wired networks, or even to wireless networks where there are some mobile nodes but with a robust communication infra-structure, are not appliable to a scenario with such dynamic topology and severe restrictions like in MANETs.This work's goal is to develop a Publish/Subscribe architecture capable of making use of MANETs' nodes own mobility to help the task of delivering submitted publications to every interested node. Mobility is used making publications received locally to be forwarded in different regions of the network after these nodes move. Therefore, with sufficient movement, publications can be disseminate through the whole network.Results have shown that the proposed architecture had a better performance then other solutions in the literature. Besides that, it was made clear that the proposed architecture is flexible enough to adapt to applications with distinct requirements.